Cytotoxicities and Quantitative Structure Activity Relationships of B13 Sulfonamides in HT-29 and A549 Cells - Lee, Seul Ki Chan (The Korean Physiological Society and The Korean Society of Pharmacology, 2011)
B13 analogues are being considered as therapeutic agents for cancer cells, since B13 is a ceramide analogue and inhibits ceramidase to promote apoptosis in cancer cells. B13 sulfonamides are assumed to have biological activity similar to B13, since they are made by bioisosterically substituting the carboxyl moiety of B13 with sulfone group. Twenty B13 sulfonamides were evaluated for their in vitro cytotoxicities against human colon cancer HT-29 and lung cancer A549 cell lines using MTT assays. Replacement of the amide group with a sulfonamide group increased cytotoxicity in both cancer cell lines. The sulfonamides with long alkyl chains exhibited activities two to three times more potent than that of B13 and compound (15) had the most potent activity with IC50 values of 27 and 28.7µM for HT-29 and A549, respectively. The comparative molecular field analysis (CoMFA) and comparative molecular similarity indices analysis (CoMSIA) were used to carry out QSAR molecular modeling of these compounds. The predictive CoMSIA models for HT-29 and A549 gave cross-validated q2 values of 0.703 and 0.830, respectively. From graphical analysis of these models, we suppose that the stereochemistry of 1,3-propandiol is not important for activity and that introduction of a sulfonamide group and long alkyl chains into B13 can increase cytotoxicity.